Obtenção e caracterização de amido termoplástico: um estudo da sua termodegradação e fotodegradação após exposição à radiação Ultra Violeta - RAMOS JÚNIOR, Gilberto Sérgio da Silva (2023)
Faced with the intense disposal of plastic materials into the environment, researchers began to give more importance to the use of polymers from renewable resources. Starch-based materials, for example, can bring good results because they are an abundant, cheap and biodegradable material. The objective of this work was to develop, characterize and observe the aging behavior in contact with ultraviolet radiation of polymers in film format, with corn starch in its base composition. The films were produced by casting technique using commercial corn starch and glycerol as plasticizer. Six types of specimens were produced, with different percentages of glycerin in their composition, which were subjected to a tensile test in accordance with ASTM D882-02. Seeking to understand among them which has better property of resistance to traction and deformation. The corn starch films were morphologically characterized (SEM and XRD) and underwent thermal analysis (TGA, DTG and DSC), before and after the samples were exposed to ultraviolet radiation, seeking to compare what the literature proposes about the effects of such form of degradation in this class of polymers. The XRD results revealed that, when photodegraded with Ultraviolet light, there is partial crystallization of the starch, making the material visibly darker and with a drier appearance, according to results in the literature. The results (SEM, TGA, DTG and DSC) obtained for the polymer also proved to be in agreement with those indicated in the literature. Films with 18% glycerol in their base composition showed the best tension results, however films with 25% glycerol showed the best tensile versus deformation results.